Feasibility of Child-Resistant and Senior-Friendly Press-Through Packages: Potential of Different Materials - Kiyomi Sadamoto; Hiroyuki Ura; Mikio Murata; Masaho Hayashi; Kiyoshi Kubota (MDPI AG, 2023)
Press-through packaging (PTP) is the most common type of drug packaging in Japan, and a production procedure for PTP has been established at an acceptable cost. However, unknown problems and new needs with regard to safety among users of various age-groups still need to be examined. Considering accident reports involving children and older adults, the safety and quality of PTP and new forms of PTP, such as child-resistant and senior-friendly (CRSF) packaging, should be evaluated. We conducted an ergonomic study on children and older adults to compare types of commonly used PTP and new varieties of PTP. Opening tests were attempted by children and older adults using a common type of PTP (Type A) and child-resistant (CR) PTP (Types B1 and B2) made from soft aluminum foil. The same opening test was conducted on older patients with rheumatoid arthritis (RA). The results showed that CR PTP was difficult for children to open: only 1 out of 18 children could open Type B1. On the other hand, all eight of the older adults could open Type B1, and eight patients with RA could easily open Types B1 and B2. These findings suggest that the quality of CRSF PTP can be improved with the use of new materials.